APOBEC3G protects the genome of human cultured cells and mice from radiation‐induced damage. (25th November 2022) - Britan‐Rosich, Yelena; Ma, Jing; Kotler, Eran; Hassan, Faizan; Botvinnik, Alexander; Smith, Yoav; Moshel, Ofra; Nasereddin, Abed; Sharma, Gunjan; Pikarsky, Eli; Ross, Susan; Kotler, Moshe
Abstract : Cytosine deaminases AID/APOBEC proteins act as potent nucleic acid editors, playing important roles in innate and adaptive immunity. However, the mutagenic effects of some of these proteins compromise genomic integrity and may promote tumorigenesis. Here, we demonstrate that human APOBEC3G (A3G), in addition to its role in innate immunity, promotes repair of double‐strand breaks (DSBs) in vitro and in vivo . Transgenic mice expressing A3G successfully survived lethal irradiation, whereas wild‐type controls quickly succumbed to radiation syndrome. Mass spectrometric analyses identified the differential upregulation of a plethora of proteins involved in DSB repair pathways in A3G ‐expressing cells early following irradiation to facilitate repair. Importantly, we find that A3G not only accelerates DSB repair but also promotes deamination‐dependent error‐free rejoining. These findings have two implications: (a) strategies aimed at inhibiting A3G may improve the efficacy of genotoxic therapies used to cure malignant tumours; and (b) enhancing A3G activity may reduce acute radiation syndrome in individuals exposed to ionizing radiation. Abstract : A3G protects mice from IR‐induced damage and promotes accurate DNA double‐strand breaks repair in cultured cells. Transgenic mice expressing A3G successfully survived lethal irradiation, whereas wild‐type controls quickly succumbed to radiation syndrome. In cultured cells, A3G accelerates DSB repair and promotes survival of cells after irradiation. Moreover, in a cell‐based non‐homologous end‐joining reporter system, A3G promotes deamination‐dependent error‐free rejoining of the induced double‐strand break mediated by I‐SceI.